Enhanced removal of phosphate and nitrate ions from aqueous media using nanosized lanthanum hydrous doped on magnetic graphene nanocomposite. (15th July 2017) - Rashidi Nodeh, Hamid; Sereshti, Hassan; Zamiri Afsharian, Elham; Nouri, Nina
Abstract: A novel nanocomposite adsorbent based on nanosized lanthanum hydroxide doped onto magnetic reduced graphene oxide (MG@La) was synthesized and used for removal of phosphate and nitrate ions from river and sewage media. The composition, surface properties and morphology of the as prepared adsorbent were studied using Fourier transform-infrared spectroscopy (FT-IR), X-ray diffraction (XRD), and field emission scanning electron microscopy (FE-SEM). The influence of main parameters on the efficiency of removal process including adsorbent dosage, salt addition, solution pH, contact time, and concentration of the analytes were thoroughly investigated. The validity of the experimental process was checked by the adsorption isotherm and adsorption kinetics models. The obtained data were well fitted to Langmuir isotherm and pseudo-second-order kinetic models. The developed adsorbent showed high adsorption capacities of 116.28 mg g −1 and 138.88 mg g −1 for phosphate and nitrate ions, respectively. Additionally, Langmuir isotherm and free energy were suggested monolayer pattern and physisorption mechanism for adsorption process, respectively. Finally, the field application of newly synthesized MG@La provided high removal efficiencies (74%–90%) for phosphate and nitrate ions in real river and sewage water samples. Highlights: A novel magnetic graphene-based lanthanum hydroxide nanocomposite was synthesized. Adsorbent used for PO4 3- and NO3 − batch adsorption from river and sewage water. Langmuir capacity for PO4 3- and NO3 − were 116.28 and 138.88 mg g −1 respectively.